Efficacy of traumatic memory reactivation with or without propranolol in PTSD with high dissociative experiences - Pascal Roullet; Simon Taïb; Claire Thalamas; Guillaume Vaiva; Wissam El Hage; Antoine Yrondi; Philippe Birmes (European Journal of Psychotraumatology, 2022)
Background: Post-traumatic stress disorder (PTSD) with dissociative symptoms is now a full-fledged subtype of this disorder. The dissociative subtype is associated with a greater number of psychiatric comorbidities. To date, the impact of dissociation on the efficacy of PTSD treatment remains unclear. Objective: The aim of this study was to compare the efficacy of a traumatic memory reactivation procedure with the administration of propranolol or a placebo once a week for six consecutive weeks in reducing PTSD and MDE symptoms between PTSD subjects with or without high dissociative symptoms. Method: For that, we conducted a randomized clinical trial in 66 adults diagnosed with longstanding PTSD and measured the SCID PTSD module, the PTSD Checklist (PCL-S), Beck’s Depression Inventory-II (BDI-II), and the Dissociative Experiences Scale (DES). Results: Patients with and without high dissociative experience had significant improvement in their PCL-S scores over the 6 treatment sessions, and PCL-S scores continued to decline in all patients during the post-treatment period. However, there was no correlation between the presence/absence of high dissociative experiences and no specific effect of propranolol treatment. We found exactly the same results for MDE symptoms. Interestingly, patients with high dissociative experiences before treatment exhibited very significant improvement in their DES scores after the 6 treatment sessions, and patients maintained this improvement 3 months post-treatment. Conclusions: The traumatic memory reactivation procedure is an effective way to treat dissociative symptoms in patients with PTSD, and improvement of these dissociative symptoms was associated with a decrease in both PTSD and depression severity.